2016
DOI: 10.17957/ijab/15.0148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Enhanced Ultraviolet-B Radiation on Chromosomes and Microtubule Arrays in Wheat Roots

Abstract: To cite this paper: Chen, P.X., H. Chen and R. Han, 2016 AbstractEnhanced ultraviolet-B (UV-B) radiation causes chromosomal aberrations and abnormal microtubule arrays in wheat (Triticum aestivum) root cells. Oryzalin induces chromosome doubling through depolymerization of microtubules and results in diploidization. We explored the effect of oryzalin on wheat roots exposed to enhanced UV-B radiation. Treatment with 500 µmol·L −1 oryzalin resulted in chromosome doubling with two equal nuclei. However, exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…This ring chromosomes in wheat maybe attributed to the large size of chromosomes, presumably large segment of chromosomes were involved in interchanges or the event of translocation. Similar observation was also observed by enhanced UV-B radiation on wheat roots with polykaryocytes and ring chromosomes (20).…”
Section: Cytological Investigationssupporting
confidence: 84%
“…This ring chromosomes in wheat maybe attributed to the large size of chromosomes, presumably large segment of chromosomes were involved in interchanges or the event of translocation. Similar observation was also observed by enhanced UV-B radiation on wheat roots with polykaryocytes and ring chromosomes (20).…”
Section: Cytological Investigationssupporting
confidence: 84%
“…In addition, similar abnormal MT arrangement and chromosome aberrations have been observed in wheat roots exposed to UV‐B radiation (Chen et al . 2016). However, the underlying mechanism behind the impact of UV‐B radiation on MT has not been reported, and the susceptor and perceptor populations of MT for UV‐B radiation are not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that spindle MT converged in several discrete sites and non-spindle MT were observed in metaphase in wheat root tips after UV-B treatment (Guo et al 2010). In addition, UV-B radiation induced abnormal MT arrays, including asymmetric PPB, asymmetric spindle/nonspindle MT and defective phragmoplasts in wheat root tips (Chen et al 2016). Under UV-B exposure (13.6-68.0 KJÁm À2 ), randomization and depolymerization of MT were observed in both epidermal and cortical cells of root tips, meristematic and elongation zones, and differentiation zones in gfp-map4 A. thaliana seedlings (Krasylenko et al 2012b).…”
Section: The Impact Of Uv-b Radiation On Mt Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Colchicine is the mainly used anti-mitotic agent [Lim and Earle 2009, Galazka and Niemirowicz-Szczytt 2013, Aslam et al 2017 along with chromosome duplication methods categorized as immersion of whole plantlets or nodal explants Abak 1996, Caglar andAbak 1997], treatment on apical meristems [Nikolova and Niemirowicz-Szczytt 1996], shoot tips Sari 2003, Solmaz et al 2011] and lateral shoots in Cucurbits. Trifluralin, amiprophos methyl, and oryzalin have been reported as alternative antimitotic agents for colchicines due to less phytotoxicity, high efficiency at low concentration, and insignificantly morphological abnormalities [Grzebelus and Adamus 2004, Alan et al 2007, Chen et al 2016.…”
Section: Introductionmentioning
confidence: 99%